A Longitudinal Electromyography Study of Complex Movements in Poststroke Therapy. 1: Heterogeneous Changes Despite Consistent Improvements in Clinical Assessments - Hesam-Shariati, Negin; Trinh, Terry; Thompson-Butel, Angelica G.; Shiner, Christine T.; McNulty, Penelope A. (Frontiers in Neurology, 2017)
Post-stroke weakness on the more-affected side may arise from reduced corticospinal drive, disuse muscle atrophy, spasticity, and abnormal co-ordination. This study investigated changes in muscle activation patterns to understand therapy-induced improvements in motor-function in chronic stroke compared to clinical assessments, and to identify the effect of motor-function level on muscle activation changes. Electromyography (EMG) was recorded from 5 upper-limb muscles on the more-affected side of 24 patients during early- and late-therapy sessions of an intensive 14-day program of Wii-based Movement Therapy, and for a subset of 13 patients at 6-month follow-up. Patients were classified according to residual voluntary motor capacity with low, moderate or high motor-function. The area under the curve was calculated from EMG amplitude and movement duration. Clinical assessments of upper-limb motor-function pre- and post-therapy included the Wolf Motor Function Test, Fugl-Meyer Assessment and Motor Activity Log Quality of Movement scale. Clinical assessments improved over time (p<0.01) with an effect of motor-function level (p<0.001). The pattern of EMG change by late-therapy was complex and variable, with differences between patients with low compared to moderate or high motor-function. The area under the curve (p=0.028) and peak amplitude (p=0.043) during Wii-tennis backhand increased for patients with low motor-function whereas EMG decreased for patients with moderate and high motor-function. The reductions included: movement duration during Wii-golf (p=0.048, moderate; p=0.026, high), and Wii-tennis backhand (p=0.046, moderate; p=0.023, high) and forehand (p=0.009, high); and the area under the curve during Wii-golf (p=0.018, moderate) and Wii-baseball (p=0.036, moderate). For the pooled data over time there was an effect of motor-function (p=0.016) and an interaction between time and motor-function (p=0.009) for Wii-golf movement duration. Wii-baseball movement duration decreased as a function of time (p=0.022). There was an effect on Wii-tennis forehand duration for time (p=0.002) and interaction of time and motor-function (p=0.005); and an effect of motor-function level on the area under the curve (p=0.034) for Wii-golf. This study demonstrated different patterns of EMG changes according to residual voluntary motor-function levels despite heterogeneity within each level that was not evident following clinical assessments alone. Thus, rehabilitation efficacy might be underestimated by analyses of pooled data.